2019
DOI: 10.1002/we.2361
|View full text |Cite
|
Sign up to set email alerts
|

Laminar‐turbulent transition detection on airfoils by high‐frequency microphone measurements

Abstract: In the present work, various data processing methods for laminar to turbulent transition detection on airfoils are assessed based on experimental data. For this purpose, NACA 63-418 airfoil profile with surface microphones flush mounted both on the suction and the pressure side is used in the wind tunnel experiments. Reynolds numbers are changed in the range from 1.6 · 10 6 to 6 · 10 6 for various angles of attack. In this way, the transition behaviour of the airfoil is characterized.Time signals and spectrogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…The x tr p is shown on the upper graph of Fig. 8 in comparison with the results from wind tunnel testing at Re 5 mill on the similar 2D airfoil section model as presented in [12]. A considerable shift of x tr p towards higher AoA is seen which amounts to 8 to 10 deg when x tr p is close to the LE.…”
Section: Rotor Transition Compared With Transition On the Blade Sementioning
confidence: 75%
See 4 more Smart Citations
“…The x tr p is shown on the upper graph of Fig. 8 in comparison with the results from wind tunnel testing at Re 5 mill on the similar 2D airfoil section model as presented in [12]. A considerable shift of x tr p towards higher AoA is seen which amounts to 8 to 10 deg when x tr p is close to the LE.…”
Section: Rotor Transition Compared With Transition On the Blade Sementioning
confidence: 75%
“…8 shows the comparison of rotor vs. wind tunnel transition results for the suction side. Again the wind tunnel results are from [12] where it was found that the transition was shifted towards lower AoA than e.g predictions by Xfoil indicated. The causes were also discussed and a combination of interaction from neighbouring/upstream microphones and the surface irregularities were mentioned as possible effects.…”
Section: Rotor Transition Compared With Transition On the Blade Sementioning
confidence: 80%
See 3 more Smart Citations